2012
DOI: 10.2117/psysoc.2012.227
|View full text |Cite
|
Sign up to set email alerts
|

Amodal Completion of Boundaries in Coloured Surfaces

Abstract: We present an experimental study on the influence of colour and spatial position in the assessment of boundaries in occluded surfaces. Subjects were asked to mark the place that they judged to be the location of a boundary between two differently coloured parts of a vertical rectangle partially occluded by a horizontal rectangle. Besides the use of eight pairs of colours, the position of the occluder was randomly changed resulting in 13 possible sizes of the coloured parts. The same colours were set for half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 104 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…These basic findings already show that amodal completion can be influenced by the visible colours in the occlusion pattern. In addition, these results are consistent with previous findings that surface characteristics, more specifically colour, play a role in amodal completion (Dadam et al, 2012;Kim et al, 2014;Pinna, 2008;Su et al, 2010;Yin et al, 1997). Next, we proposed an analysis in which we had a closer look at the net effect of colour context, i.e., the colour context analyses.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These basic findings already show that amodal completion can be influenced by the visible colours in the occlusion pattern. In addition, these results are consistent with previous findings that surface characteristics, more specifically colour, play a role in amodal completion (Dadam et al, 2012;Kim et al, 2014;Pinna, 2008;Su et al, 2010;Yin et al, 1997). Next, we proposed an analysis in which we had a closer look at the net effect of colour context, i.e., the colour context analyses.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies have focused on volume completion (Ekroll, Sayim, & Wagemans, 2013;Ekroll, Sayim, Van Der Hallen, & Wagemans, 2016;Tse, 1999a;Tse, 1999bTse, , 2017van Lier, 1999;van Lier & Wagemans, 1999;Vrins, de Wit, & van Lier, 2009;Vrins, Hunnius, & van Lier, 2011). Rather few studies looked at the influences of inner surface properties in amodal completion (e.g., Dadam, Albertazzi, Canal, & Micciolo, 2012;Su, He, & Ooi, 2010). For example, Dadam et al (2012) reported that contrast characteristics influenced the relative position of an amodally completed border; in specific displays, partly occluded bars tended to extend more behind an occluder when they were relatively dark (as compared to lighter bars).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This representation of occluded objects has been a topic of interest in several fields investigating situations of both partial and full occlusion. Behavioral studies investigating amodal completion -the process of filling in occluded parts of an object -have shown that both the shape (Rensink & Enns, 1998) and color (Albertazzi, Canal, & Micciolo, 2012;Pinna, 2008) are completed for the occluded segment of the object. This representation of the occluded segment is formed automatically (Murray, Imber, Javitt, & Foxe, 2006) and can influence both the interpretation of concurrent events (Joseph & Nakayama, 1999;Sekuler & Palmer, 1992) as well as subsequent behavior (Gerbino & Salmaso, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies investigating amodal completion -the process of filling in occluded parts of an object -have shown that both the shape (Rensink & Enns, 1998) and color (Dadam, Albertazzi, Canal, & Micciolo, 2012;Pinna, 2008) are completed for the occluded segment of the object. This representation of the occluded segment is formed automatically (M. M. Murray et al, 2006) and can influence both the interpretation of concurrent events (Joseph & Nakayama, 1999;Sekuler & Palmer, 1992) as well as subsequent behavior (Gerbino & Salmaso, 1987).…”
Section: Introductionmentioning
confidence: 99%